Pyrrhonian Relativism - Machuca, Diego Emanuel (2015)
This paper argues that Sextus Empiricus’s Pyrrhonism is a form of relativism markedly different from the positions typically referred to by this term. The scholars who have explored the relativistic elements found in Sextus’s texts have claimed that his outlook is not actually a form of relativism, or that those elements are inconsistent with his account of Pyrrhonism, or that he is confusing skepticism with relativism. The reason for these views is twofold: first, when employing the term ‘relativism’ one hardly has in mind the sort of relativist stance adopted by the Pyrrhonist; and second, those scholars have misinterpreted Sextus’s relativistic remarks. The purpose of this paper is to show that he adopts a ‘phenomenological’ kind of relativism that is compatible with his account of Pyrrhonism